Tek Millet, Nationalism Religious Edoganism - Sujibto, B.J. (JURNAL PENELITIAN, 2019)
This article aims at examining forms and characteristics of Turkish nationalism under Erdoganism, a relatively new term which has been devoted to leadership of Recep Tayyip Erdogan. The notion of nationalism has not been the main focus on the full range of the political rhetoric and the social interactions demonstrated by Erdogan. However, generally considered as a fundamental element in Turkey's social and political development, nationalism always remains a hot topic which cannot be separated from social dynamics and society itself. For this reason, nationalism will endlessly continue to look for a dynamic form and, at the same time, becomes an instrument of the ruling to control the distribution of power. Erdoganism itself has various distinct approaches towards the narrative and development of Turkish nationalism. This research used a qualitative approach with discourse analysis method by elaborating symbols, languages, writings, and speeches demonstrated by Erdogan in the political activities. The findings of this research are expected to be able to comprehend nationalism of Erdoganism.